Peroxisome proliferator‐activated receptor gamma (PPARγ) is central to the initiation and propagation of human angiomyolipoma, suggesting its potential as a therapeutic target. Issue 12 (1st December 2017) - Pleniceanu, Oren; Shukrun, Racheli; Omer, Dorit; Vax, Einav; Kanter, Itamar; Dziedzic, Klaudyna; Pode‐Shakked, Naomi; Mark‐Daniei, Michal; Pri‐Chen, Sara; Gnatek, Yehudit; Alfandary, Hadas; Varda‐Bloom, Nira; et al.
Abstract :